Produktivni model v življenskem ciklu gradbenega objekta - Rebolj, Danijel (Uporabna informatika (Ljubljana), 1999)
The intention the paper is to present problems and solutions in integrating information flows in the life cycle of a building object. Although many life cycle phases have already been supported by more or less suitable information technology, these "islands of automation" are not suitably integrated. The paper describes an already recognized solution concept, based on the integrated product model, and explains it on a simple product model of a road.Positive effects as well as some deficiencies of product models are shown. The article ends with a description of a new concept of "virtual product model", overcoming some of the stated deficiencies.
Keywords: gradbena informatika; gradbeništvo; informacijska tehnologija; modeli